2015
DOI: 10.1002/2014gb004906
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of biological and physical controls on surface ocean CO2 from hourly observations at the Southern Ocean Time Series site south of Australia

Abstract: The Subantarctic Zone (SAZ), which covers the northern half of the Southern Ocean between the Subtropical and Subantarctic Fronts, is important for air-sea CO 2 exchange, ventilation of the lower thermocline, and nutrient supply for global ocean productivity. Here we present the first high-resolution autonomous observations of mixed layer CO 2 partial pressure (pCO 2 ) and hydrographic properties covering a full annual cycle in the SAZ. The amplitude of the seasonal cycle in pCO 2 (∼60 μatm), from near-atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(113 citation statements)
references
References 76 publications
9
88
2
Order By: Relevance
“…Li and Peng, 2002;Najjar, 2009). Metzl et al (1999) and Shadwick et al (2015) observed that the uptake of CO 2 over the sub-Antarctic zone (SAZ, between the SAF and the STF) in summer is mostly controlled by biological processes. If a change in remineralisation rates has occurred, i.e.…”
Section: Circulation and Biological Processes At Steady Statementioning
confidence: 99%
“…Li and Peng, 2002;Najjar, 2009). Metzl et al (1999) and Shadwick et al (2015) observed that the uptake of CO 2 over the sub-Antarctic zone (SAZ, between the SAF and the STF) in summer is mostly controlled by biological processes. If a change in remineralisation rates has occurred, i.e.…”
Section: Circulation and Biological Processes At Steady Statementioning
confidence: 99%
“…Figure 3 indicates how inconsistent Southern Ocean pCO 2 data density is in space and time. Even given the sampling efforts of the DPT, repeated occupations of SR03 south of Australia [Shadwick et al 2015], along…”
Section: !mentioning
confidence: 99%
“…Measurements of the annual production of oxygen [ Riser and Johnson , ; Bushinsky and Emerson , ] or depletion of nitrate [ Plant et al ., ] using sensors mounted on profiling floats can provide direct estimates of ANCP after the Redfield ratio is used to convert the measured quantity to carbon uptake. While these sensors can be deployed on a variety of other platforms, such as moorings [ Shadwick et al ., ] or gliders [ Nicholson et al ., ], the high operational costs of these platforms [ Rudnick et al ., ] generally preclude large arrays from being deployed [ Rudnick , ]. The Argo program [ Riser et al ., ] has demonstrated that very large arrays of profiling floats can be operated at the global scale.…”
Section: Introductionmentioning
confidence: 99%